Trabajo y sujeto : un acercamiento desde Alejandro López (2003)
ABSTRACT: This paper pretends to provide some elements of analysis on the complex matter of work, as seen from the point of view of Alejandro López (specifically his 1928 text "The Work"), and supported on some basic Freudian psychoanalysis notions such as need, demand and desire. Without deepening on the analysis of the context that surrounds the proposals of the author from Antioquia, it deals with the underlying tension between work as exploitation and work as a social link. Notwithstanding the difficulty of focusing on the individual in the context of the dominant economical trends, this writing studies the possibility of conceiving organizations as systems that take into account both the individual and the collectivity, a reiterative concept in López upon which he sketches a different role for the individuals in their working experience.